2022
DOI: 10.3390/jcm11092424
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Functional Impact of Acute SARS-CoV-2 Infection in Hospitalized Patients

Abstract: Aim: To assess the prevalence of malnutrition, frailty, and sarcopenia and the relationships between them in patients hospitalized for COVID-19. Methods: This was a cross-sectional study of the prevalence, determinants, and associations between malnutrition (GLIM 2019 criteria), sarcopenia (SARC-F scale, dynamometry, and calf circumference), and frailty (FRAIL scale) upon discharge following hospitalization for COVID 19. Results: A total of 101 patients (67.3% men, mean age 66.3 years) were recruited. Malnutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
2
4
0
Order By: Relevance
“…In older patients with COVID-19, rather than disease severity, the effect of prolonged immobilization due to extended hospital stay, reduced nutritional intake, and isolation could further trigger the occurrence of new disability. Notably, patients losing ADL had a significantly more extended hospital stay than their counterparts, in agreement with a recent study by Gómez-Uranga et al [ 9 ], demonstrating how frailty is related to longer hospitalization for COVID-19, harming nutritional and functional status following hospital discharge. Accordingly, in the present study, we observed the presence of a persistent functional disability in one-fifth of patients following hospital discharge, thus underlying the possibility of including the functional loss in the definition of the Long COVID symptoms in older adults.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In older patients with COVID-19, rather than disease severity, the effect of prolonged immobilization due to extended hospital stay, reduced nutritional intake, and isolation could further trigger the occurrence of new disability. Notably, patients losing ADL had a significantly more extended hospital stay than their counterparts, in agreement with a recent study by Gómez-Uranga et al [ 9 ], demonstrating how frailty is related to longer hospitalization for COVID-19, harming nutritional and functional status following hospital discharge. Accordingly, in the present study, we observed the presence of a persistent functional disability in one-fifth of patients following hospital discharge, thus underlying the possibility of including the functional loss in the definition of the Long COVID symptoms in older adults.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, loss of autonomy in basic activities, known as activities of daily living (ADL), is strongly associated with institutionalization and death [ 8 ]. In this setting, a recent study showed that hospitalization for acute SARS-CoV-2 infection harmed older patients’ functional autonomy, especially in those with severe disease and more impaired basal ADLs [ 9 ]. Nonetheless, albeit even the loss of a single ADL function is associated with an increased likelihood of requiring long-term nursing care [ 10 ] and poor outcomes [ 11 ], far too little attention has been devoted to the loss of functionality after hospitalization for COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Confirming previous studies [ 25 ], malnutrition as defined using the GLIM definition [ 18 , 19 ], was present in many of our patients and people registered in GIR 1 are more affected by the risk of malnutrition [ 26 ], and in a study investigating 4520 residents, residents who were malnourished showed an increase in overall dependency, including during mealtimes and while walking, which are major activities of daily living [ 27 ]. This reinforces the link between malnutrition and a patient’s functional status, including frailty and dependency [ 28 , 29 , 30 ].…”
Section: Discussionsupporting
confidence: 55%
“…An analysis of the disease as such takes into account not only the infectious variables but also the social and nutritional variables and comorbidities, revealing biological and social interactions that are important for prognosis, treatment, and health policy [ 13 , 40 , 41 , 42 ]. Albumin could be a good prognostic marker because it is a global indicator of individual susceptibility, bringing together the influence of comorbidities, anti-inflammatory reactions to infection, markers of systemic inflammation [ 10 , 11 , 12 ], and nutritional status [ 54 ]. Thus, SA could explain the association between comorbidity, one of the most important determinants of the course of COVID-19, and poor prognosis [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%